2021
DOI: 10.3390/scipharm89020020
|View full text |Cite
|
Sign up to set email alerts
|

Docking-Based Virtual Screening and Molecular Dynamics Simulations of Quercetin Analogs as Enoyl-Acyl Carrier Protein Reductase (InhA) Inhibitors of Mycobacterium tuberculosis

Abstract: The emergence of multidrug-resistant Mycobacterium tuberculosis (MTB) has become a major problem in treating tuberculosis (TB) and shows the need to develop new and efficient drugs for better TB control. This study aimed to use in silico techniques to discover potential inhibitors to the Enoyl-[acyl-carrier-protein] reductase (InhA), which controls mycobacterial cell wall construction. Initially, 391 quercetin analogs present in the KNApSAck_3D database were selected, filters were sequentially applied by docki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 29 publications
0
11
0
2
Order By: Relevance
“…The best ligand as observed from the result is ZINC ID:05220992 (named as C-992) which was used for experimental validation. Several reports showed that using idock score people screened inhibitor (idock score≤ -8 kcal/mol) molecules against various receptors and worked well as per experimental validation report [27,28]. In this context, our screened compound showing a better idock score and RF score (-10.17 kcal/mol, 6.22 pKd).…”
Section: Methodsmentioning
confidence: 57%
“…The best ligand as observed from the result is ZINC ID:05220992 (named as C-992) which was used for experimental validation. Several reports showed that using idock score people screened inhibitor (idock score≤ -8 kcal/mol) molecules against various receptors and worked well as per experimental validation report [27,28]. In this context, our screened compound showing a better idock score and RF score (-10.17 kcal/mol, 6.22 pKd).…”
Section: Methodsmentioning
confidence: 57%
“…Meanwhile, the average RMSD fluctuations for each system, namely, minoxidil, finasteride, and bufotalinin, were 0.206, 0.203, and 0.211, respectively. The average RMSD showed that bufotalinin had the lowest fluctuation compared to the reference ligand, which indicates that the ligand has reached a stable conformation that binds to the protein [ 29 ]. The amino acid fluctuations of the two receptor complex systems calculated by RMSF showed the same pattern in all regions.…”
Section: Resultsmentioning
confidence: 99%
“…The SASA of the androgen receptor–ligand complex on the graph for bufotalinin showed similar fluctuations, which were higher than those for minoxidil and finasteride; the average values for minoxidil, finasteride, and bufotalinin were 120.13, 115.93, and 117.96 nm 2 , respectively. A low SASA value indicates an increasingly stable complex system [ 29 ]. This analysis correlated with that of the RMSD value, which indicated that bufotalinin had better stability at the androgen receptor than minoxidil and finasteride.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the 2D projection plot of PCA is another method to illustrate the dynamics of a protein in the essential subspace of the system [76]. Noteworthily, the protein-ligand system occupying less space was more stable, whereas the largely occupied system was less stable [77]. From Figure 8c, we observed that the overall motion of the ACCase-FPPE complex was confined within the eigenvalues ranging from −18 to 13 nm and −9 to 18 nm along with the projection of eigenvector1 and eigenvector2.…”
Section: Essential Dynamicsmentioning
confidence: 99%